2020
DOI: 10.1038/s41598-020-58732-x
|View full text |Cite
|
Sign up to set email alerts
|

Autologous platelet-rich fibrin stimulates canine periodontal regeneration

Abstract: Platelet-rich fibrin (PRF) provides a scaffold for cell migration and growth factors for promoting wound healing and tissue regeneration. Here, we report using PRF in periodontal healing after open flap debridement (OFD) in canine periodontitis. A split-mouth design was performed in twenty dogs. Forty periodontitis surgical sites were randomly categorized into 2 groups; OFD alone and OFD with PRF treatment. Clinical parameters of periodontal pocket depth, gingival index, and the cemento-enamel junction-alveola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 73 publications
1
25
0
7
Order By: Relevance
“…Some laboratory studies were carried out on platelets and leukocyte contents, and on the amount of GFs in both standard and advanced PRF in humans [11,12,[60][61][62]. Several studies have reported the amount of GFs in canine PRF; however, to the authors' knowledge, a complete characterization of the canine PRF has not yet been performed [46,52,63].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some laboratory studies were carried out on platelets and leukocyte contents, and on the amount of GFs in both standard and advanced PRF in humans [11,12,[60][61][62]. Several studies have reported the amount of GFs in canine PRF; however, to the authors' knowledge, a complete characterization of the canine PRF has not yet been performed [46,52,63].…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, the PRF has been tested on the healing of canine extraction sockets and in peri-implant sites, however all of these studies were experimental; therefore, lesions and tooth extractions were specially created in healthy dogs, which were used animal models for preclinical purposes [45][46][47][48][49][50][51][52][53].…”
Section: Introductionmentioning
confidence: 99%
“…Autologous platelet rich fibrin was chosen to improve periodontal regeneration 26 , 27 . The study in dogs demonstrated that the combination of autologous PRF with open flap debridement improved periodontal pocket depth and cemento-enamel-junction-alveolar bone levels/root length ratio 15 . In addition, the inflammatory score was decreased in open flap debridement with PRF application compared with the control 15 , implying the beneficial utilization of PRF in periodontal regenerative treatment.…”
Section: Discussionmentioning
confidence: 95%
“…The preparation of PRF is an easy and cost-effective way in clinical use in human study. Our previous report demonstrated the use of autologous PRF in periodontal regenerative treatment in dogs 15 . However, a high-volume collection of autologous blood in small dog breeds has technical difficulty.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with chronic periodontitis, the use of 1% metformin and PRF showed more pocket depth reduction and relative attachment level than either group alone [ 283 ]. Along with open-flap debridement, PRF has been shown to increase canine periodontitis treatment outcomes in animal studies [ 284 ].…”
Section: Biomimetics Of Periodontal Tissue Engineering and Regenermentioning
confidence: 99%